How do foreign currency derivatives impact firm value: empirical evidence from industrial firms in Asian countries - Lim, Li Chern (2019)
Empirical research has shown that derivatives have significant impact on firm value. However, the relationship between use of derivatives and firm value is still vague as some studies have indicated a positive relationship while other studies have indicated otherwise. This empirical study aims to contribute to the literature of derivative use by further examining how derivatives impact firm value. The research design behind this investigation employs a hand-collected dataset encompassing a sample of 130 industrial firms from Hong Kong, Singapore, Malaysia and Taiwan from the period of 2008 to 2017. By examining how firms hedge long-term and short term foreign currency exposures with foreign currency derivatives, a clearer picture can be obtained regarding the hedging strategies on Asian firms. This study also examined the effectiveness of derivative usage through comparing the derivative assets and derivative liabilities of firms. This empirical research also studied the impact of utilising foreign currency derivatives in general, as well as different types of foreign currency derivatives, on firm values. The findings in this study are also compared between developed and developing markets to assess the difference and similarities of hedging strategies and firm characteristics of sample firms in both markets. The main findings of this study are as follows. Forward foreign currency contracts are the preferred foreign currency derivative to hedge both short-term and long term foreign currency exposures. Findings also indicate that with the exception of Hong Kong firms, firms from the other countries are experiencing effective derivative hedging on currency exposures. As for the impact of foreign currency derivatives, only coefficients for Hong Kong sample firms are statistically positive and significant. As for the type of derivative contract, foreign options are the only contract which is significant in affecting firm value. However, options are viewed negatively by market participants as evidenced by the hedging discount on firm value.